Expression of the Biologically Active Insulin Analog SCI-57 in Nicotiana Benthamiana - Muñoz-Talavera, Adriana; Gómez-Lim, Miguel Ángel; Salazar-Olivo, Luis A.; Reinders, Jörg; Lim, Katharina; Escobedo-Moratilla, Abraham; López-Calleja, Alberto Cristian; Islas-Carbajal, María Cristina; Rincón-Sánchez, Ana Rosa (Frontiers in Pharmacology, 2019)
Diabetes mellitus is a growing problem worldwide; however, only 23% of low-income countries have access to insulin, and ironically it costs higher in such countries than high-income ones. Therefore, new strategies for insulin and insulin analogs production are urgently required to improve low-cost access to therapeutic products, so as to contain the diabetes epidemic. SCI-57 is an insulin analog with a greater affinity for the insulin receptor and lower thermal degradation than native insulin. It also shows native mitogenicity and insulin-like biological activity. In this work, SCI-57 was transiently expressed in the Nicotiana benthamiana (Nb) plant, and we also evaluated some of its relevant biological effects. An expression plasmid was engineered to translate an N-terminal ubiquitin and C-terminal endoplasmic reticulum-targeting signal KDEL, in order to increase protein expression and stability. Likewise, the effect of co-expression of influenza M2 ion channel (M2) on the expression of insulin analog SCI-57 (SCI-57/M2) was evaluated. Although using M2 increases yield, it tends to alter the SCI-57 amino acid sequence, possibly promoting the formation of oligomers. Purification of SCI-57 was achieved by FPLC cation exchange and ultrafiltration of N. benthamiana leaf extract (NLE). SCI-57 exerts its anti-diabetic properties by stimulating glucose uptake in adipocytes, without affecting the lipid accumulation process. Expression of the insulin analog in agroinfiltrated plants was confirmed by SDS-PAGE, RP-HPLC, and MS. Proteome changes related to the expression of heterologous proteins on N. benthamiana were not observed; up-regulated proteins were related to the agroinfiltration process. Our results demonstrate the potential for producing a biologically active insulin analog, SCI-57, by transient expression in Nb.